2019
DOI: 10.1111/ele.13419
|View full text |Cite
|
Sign up to set email alerts
|

Phenology responses of temperate butterflies to latitude depend on ecological traits

Abstract: Global change influences species’ seasonal occurrence, or phenology. In cold‐adapted insects, the activity is expected to start earlier with a warming climate, but contradictory evidence exists, and the reactions may be linked to species‐specific traits. Using data from the GBIF database, we selected 105 single‐brooded Holarctic butterflies inhabiting broad latitudinal ranges. We regressed patterns of an adult flight against latitudes of the records, controlling for altitude and year effects. Species with dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 49 publications
1
23
1
Order By: Relevance
“…Our results varied substantially in both onset and termination across species (Figure 2). In contrast to Fric et al (2020), we found significantly later and/or shorter flight periods at higher latitudes for most species. These new results were consistent with the latitudinal gradient in climate and growing season length (Kobayashi et al 2016).…”
Section: Introductioncontrasting
confidence: 92%
See 3 more Smart Citations
“…Our results varied substantially in both onset and termination across species (Figure 2). In contrast to Fric et al (2020), we found significantly later and/or shorter flight periods at higher latitudes for most species. These new results were consistent with the latitudinal gradient in climate and growing season length (Kobayashi et al 2016).…”
Section: Introductioncontrasting
confidence: 92%
“…Given these biases, proper data curation and appropriate modelling strategies are necessary to ensure valid inferences. Fric et al 2020 used occurrence data for 100 species aggregated in the Global Biodiversity Information Facility (GBIF) in temperate regions of North America and Europe to track phenology across latitudes. Estimating phenology metrics and trends from large occurrence datasets is possible, but requires sufficient data density and appropriate statistical methods (Taylor & Guralnick 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Their current ranges reach to the far North (see the sampling locations, Figures 1–4), suggesting efficient mechanisms of winter diapause (cf. Vrba et al., 2017) and an ability to capitalize on short but intensive Arctic summers (Faltynek Fric et al., 2020).…”
Section: Discussionmentioning
confidence: 99%